Strategy to Increase the Effectiveness of Capacity Building Programs for Village-Owned Enterprises - Sri Juni Woro Astuti; Arini Sulistyowati; Yanuar Fauzuddin (Yayasan Ilomata, 2023)
Various facts indicate that the capacity building program for Village Owned Enterprises (BUM Desa) is not yet optimal. The existence of BUM Desa which is spread in almost all villages in Indonesia, it turns out that only about 10% are active. Even though the Indonesian Government really hopes that the existence of Bum Desa will be able to accelerate the economic recovery of village communities after the Covid-19 pandemic. Therefore this study aims to find alternative strategies for more effective capacity building programs. The research method used is qualitative. This study took samples from three villages in East Java. Data collection through in-depth interviews, observation, FGD and documentation. The results of the study show that the three BUM Desa have not implemented modern and professional management. This indicates that the capacity building program that has been implemented has not been running effectively, so it is necessary to look for alternative strategies that can increase the effectiveness of the capacity building program. The results of the study identified village local wisdom values that could be synergized in the management of BUM Desa and received support from all stakeholders, especially the community. Finally, this research recommends that the implementation of capacity building programs for village governments be synergized with local wisdom values.